Knowledge level and health information-seeking behavior of people with diabetes in rural areas: a multicenter cross-sectional study - Wang, Yudong; Zhang, Yanping; Guo, Tingting; Han, Jiaxia; Fu, Guifen (Frontiers in Public Health, 2024)
Introduction: There is a lack of research on the current level of diabetes knowledge and health information-seeking behaviors among patients with diabetes in rural areas of China's economically underdeveloped regions during COVID-19, as well as a lack of up-to-date evidence on glycemic control and the incidence of complications among rural patients with diabetes. Objectives: To investigate the prevalence of glycemic control and complications among patients with diabetes in rural areas, to explore the current status and correlation of diabetes knowledge level and health information seeking behavior, and to analyze the factors affecting diabetes knowledge level. Methods: From January 2022 to July 2022, we conducted a screening on diabetic complications and questionnaire survey among 2178 patients with diabetes in 15 county hospitals in rural areas of Guangxi Zhuang Autonomous Region. The patients' knowledge level and health information seeking behavior were investigated. Spearman correlation analysis was used to assess the correlation between diabetes knowledge and health information seeking behavior. Multiple linear regression analysis was used to test how demographic information and health information seeking behavior influenced the level of diabetes knowledge. Results: Of 2178 patients with diabetes in rural areas, 1684 (77.32%) had poor glycemic control and the prevalence of diabetic complications was estimated to be 72.13%. Patients with diabetes had poor diabetes knowledge and health information seeking behavior, and there is a strong positive correlation between them. Diabetes knowledge level was influenced by per capita household disposable income, occupational status, gender, age, ethnicity, family history of diabetes, insulin use, glycated hemoglobin, education level, number of complications and health information seeking behavior. Conclusion: Patients with diabetes in rural areas have poor glycemic control and a high incidence of diabetic complications. Patients with diabetes in rural areas have poor knowledge and inadequate health information seeking behavior. Systematic and standardized education should be provided to improve patients' diabetes knowledge and thus improve their self-management ability.